The positive effects of ethnic diversity in class on the educational performance of pupils in a multi-ethnic European metropole - Sjaak Braster; Jaap Dronkers (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
According to Robert Putnam (2007) ethnic diversity in cities and neighborhoods does not lead to an increase of trust and social capital as previously predicted by intergroup contact theory (Pettigrew, 1998); instead it triggers a reaction of hunkering down that leads to a decrease in trust and social capital of both in-group and out-groups. But what happens if we focus on youngsters that are growing up in a multi-ethnic metropole, that are considering ethnic diversity as a something "normal", and that are bridging their ethnic differences by sharing a common street culture and language? In this article we use data about 905 pupils, 41 classes and 11 schools in a European metropole to confirm the hypothesis that in this specific context ethnic diversity in classrooms does lead to positive effects on educational performance.
Keywords: 330; ethnic diversity; educational performance; classroom effects; multi-ethnic cities